Literasi Digital Dalam Membentuk Karakter Religius Generasi Milenial (Studi tentang Pembentukan Karakter Mahasiswa PAI Universitas Muhammadiyah Gresik - Noor Amirudin (STIT Muhammadiyah Paciran Lamongan, 2022)
The current state of life in the millennial era is full of challenges and competition. This has an impact, among others, on a high level of depression in addition to the availability of opportunities for those who have life competencies, and have multiliteracy that strengthens students' physical, mental, and intellectual capacities. For that we need a way how to shape the religious character of students, especially PAI students at the University of Muhammadiyah Gresik through digital literacy?. There needs to be a method in reviewing the research in revealing the existing problems, namely by using a descriptive method with a qualitative approach, focusing on the study of the formation of religious character of PAI UMG students. The results of the study reveal that various forms of collaboration and cooperation between communities and educational units outside the campus are indispensable in strengthening religious character education. There are various forms of collaboration that can be done in the context of developing character education for PAI UMG students in facing the millennial era, namely with Islamic digital literacy activists. Such as good attitudes and intentions, namely getting used to literacy through cellphone media (HP): speaking and writing in Short Message Service (SMS) or WhatsApp (WA) that is polite when communicating, behaves well, protects the environment, and looks after the environment. order.